Construction of Welfare Mediation Model Based on Tri Hita Karana on The Economic Effect of Tourism Sector Toward Happiness To Improve Life Satisfaction of Local Community - Kusuma, I Gusti Agung Teja; Landra, Nengah; Widnyana, I Wayan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
This research aims to measure effects of tourism economy on Tri Hita Karana (Balinesse Life Philosophy) well-being including physical health and well being, psychological, relationship, and spiritual well being, to realize the well-being so that it can create life of satisfaction. Using quantitative method using existing measurement scale. Results of this research indicate thatÂ there is no significant effect of tourism economic benefit on happiness and public life of satisfaction. The economic benefit will provide effects on local public happiness and then it canÂ create life of satisfaction, if the public obtain the sense of Tri Hita Karana-based well-being. Another finding proves that Tri Hita Karana well being is proven significantly as a mediated effect of economic benefit on public happiness. Practical implication of the researchers is that the economic measurement is not adequate to be used to predict success of sustainable tourism. It is necessary for other indicators such as well-being, happiness and public life of satisfaction .This research originality and value are to fulfil research gap to involve Tri Hita Karana cultural aspect as a local wisdom trusted to have universal value in determining well-being in the field of tourism economic performance.